Studi Pencemaran Logam Berat pada Beras di Daerah Pengolahan Emas Tanpa Izin, Kecamatan Nanggung, Kabupaten Bogor - Laksmi Istikasari; Dedi Fardiaz; Nuri Andarwulan (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2017)
This research was based on the issue of environmental pollution by heavy metals originating from gold processing waste without permission in Nanggung District and its impact on rice around the location. The main purpose is to get a map of contamination of heavy metals (Pb, Cd, Cu, Fe, and Hg) in rice and find out the metal's daily intake of rice. The research consists of several stages, namely: (1) Inventory villages that have gold processing activities without permits, (2) Inventory agricultural land and location mapping, (3) Sampling and preparation of samples, (4) Analysis of heavy metals level in rice, (5) Mapping of heavy metal contamination in rice in Nanggung District. Unlicensed gold processing activities were found in seven villages in Nanggung District. Residents of Nanggung District consume rice from their own fields three times a day as much as 150-250 g. Pb levels in rice ranged from 0.44-3.69 ppm with a percentage of 52.63%, Cd was not detected in all rice. Cu content ranges from 0.01-1.19 ppm with a percentage of 78.95%. Fe in all rice with a range of 2.51-43.56 ppm. Hg levels ranged from 13.70-251.30 ppb with a percentage of 100%. Daily Pb and Hg metal intake from rice in some villages exceeded the Joint WHO/FAO Expert Committee on Food Additives (JECFA) Provisional Maximum Torelable Daily Intake (JECFA), all of which is below the PMTDI value. Total Pb and Hg daily intake in Parakan Muncang and Curug Bitung Villages has exceeded PMTDI, while total Cu and Fe intake is still below PMTDI.